Morphology of Erythrocytes and Leukocytes of the Lesser Sunda Islands Pit Viper (Trimeresurus insularis): The Green Coloration from Bali Island and the Blue Coloration from Komodo Island - Diza Pakom, Muhammad Sofi; Wandia, I Nengah; Setiasih, Ni Luh Eka; Komala Sari, Tri; Kardena, I Made; Suartini, I Gusti Ayu Agung (Jurnal Sain Veteriner, 2026)
Indonesia is a tropical country with a diverse range of herpetofauna, one of which is the Trimeresurus insularis snake, a highly venomous species endemic to Indonesia. This snake is distributed across Java, Bali, West Nusa Tenggara, East Nusa Tenggara, and Wetar Island in Maluku Province. Despite its wide distribution, this species exhibits variations in body coloration. T. insularis from Bali is green, while those from Komodo Island are blue; however, both share the same red tail. This study aims to examine the morphology and morphometry of erythrocytes and leukocytes in T. insularis from different localities and color variations. The research utilized blood smear preparations from six healthy T. insularis individuals—three green coloration from Bali and three blue coloration from Komodo Island—analyzed using a microscope and Optilab Viewer camera. Cell morphometry was measured using ImageJ software. The morphometric measurements of erythrocytes included the length and width of the cytoplasm and nucleus, while leukocyte morphometry covered the cytoplasmic and nuclear diameters of heterophils, basophils, eosinophils, azurophils, lymphocytes, and monocytes. The erythrocyte morphology of T. insularis from both Bali and Komodo Island showed no differences. Morphometric data were analyzed using the Independent-Samples T Test. The results showed significant differences in the length and width of the erythrocyte nucleus, as well as in the cytoplasmic and nuclear diameters of lymphocytes. Meanwhile, no significant differences were found in erythrocyte length and width, as well as in the cytoplasmic and nuclear diameters of heterophils, basophils, eosinophils, and monocytes.